(untitled) (Journal of Agriculture and Plant Sciences, 2013)
The purpose of these work was to extend a new contribution of knowing of pepper Aphids.The qualitative analisis it was consider that in the region of Strumica there were five species of pepper Aphids: Myzus persicae Sulz.; Aphis gossypii Glov.; Aphis fabae Scopoli; Aulacortum solani Kalt. and Macrosiphum euphorbiae Thomas. The qvantitative analysis of the Aphids was done according to it’s presents in the period of arriving and according to it’s species.It was consider that the higher presents of Aphids was noticed in the spring time, started at the second half of may till the second half of jun.In the outhom time the higher present of Aphids was noticed from the second half of the september till the second half of the october. The most freqvent species of Aphids are M. persicae with 44,34% of presents and A. gossypii with 33,81%.